THE YUGOSLAV COLONY OF EGYPT 1941 – 1951. (Heritage, 2025)
The Yugoslav community settled in Egypt had a heterogeneous composition. It consisted of mainly of Slovenes from the unliberated regions of Italy, but it also contained a considerable number of settlers from Macedonia, then Montenegro and other Serbian regions of the then Yugoslav kingdom. The most direct contact between the Yugoslav state administration and the colony in Egypt was achieved after the collapse of the resistance of the Yugoslav army and the departure of the state apparatus into exile in the Middle and Near East in April 1941. The drama of Yugoslav internal politics took place precisely in Egypt during the military rebellion that we call the ’Cairo Affair’, throughout 1942. After the arrival of the government and the king from London in October 1943, the seat of the state apparatus was moved to Cairo. With the arrival of partisan refugees and officials in the Middle East at the end of the same year and the beginning of the following year, the Yugoslav colony was forever divided into supporters of the communist movement and royalists. The confidential reports of the agents of the new communist Yugoslavia, established in 1945, on which the article is based, provide insight into the situation in the colony on a micro level. Providing us with an opportunity to observe the leading members of the community, its internal strife
Keywords: Egypt, World War II, Yugoslav colony, Yugoslav government in exile, King Peter II Karađorđević, Yugoslav royal army in exile, Yugoslav clubs.